Psychiatric trajectories across adolescence in perinatally HIV-exposed youth: the role of HIV infection and associations with viral load. (1st July 2020) - Nguyen, Nadia; Choi, C. Jean; Robbins, Reuben; Korich, Rehema; Raymond, Jeanette; Dolezal, Curtis; Leu, Cheng-Shiun; Wiznia, Andrew; Abrams, Elaine J.; Mellins, Claude A.
Abstract : Objective: Identify factors associated with trajectories of psychiatric disorder among 340 adolescents and young adults (AYA) living with perinatal HIV infection (PHIV) and perinatal HIV-exposure but not infection (PHEU). Design: Longitudinal cohort study of AYA in New York City, 9–16 years at enrollment. Methods: We used multivariate longitudinal latent class analysis to identify trajectories of psychiatric disorder, and logistic regression to examine predictors of trajectories (e.g. PHIV status) and associations between trajectories and viremia in young adulthood (AYA with PHIV only). Results: Among all AYA, we identified three psychiatric trajectories: relatively 'low disorder' (63%), 'consistent anxiety' (26%), and 'escalating comorbidity' (11%). Compared with AYA with 'low disorder', AYA with 'escalating comorbidity' were significantly older, reported more neighborhood stress, and lived with a caregiver with alcohol use disorder, whereas AYA with 'consistent anxiety' were more likely female individuals. Although we found no statistically significant HIV status differences, among AYA with PHIV, nearly half (48%) were viremic in young adulthood, with higher odds of viremia among AYA with 'escalating comorbidity' (OR: 3.88, 95% CI: 0.93–16.26) and 'consistent anxiety' (OR: 2.41, 95% CI: 1.011–5.75) compared with 'low disorder'. Conclusion: Despite significant adversity, AYA with PHIV and PHEU had relatively low prevalence of psychiatric disorder over time, although one-third had consistent or escalating psychiatric disorders. Among AYA with PHIV, psychiatric trajectories were associated with viremia in young adulthood. Given the growing population of AYA living with PHIV and PHEU worldwide, addressing the substantial and evolving mental health needs of both groups as they reach young adulthood is critical. Abstract : Supplemental Digital Content is available in the text